Odpornost izolatov Streptococcus pneumoniae iz dihal v letu 2003 - Štrumbelj, Iztok (Zdravstveno varstvo, 2005)
Objective: To determine resistance to selected antibiotics in respiratory tract isolates of Streptococcus pneumoniae in year 2003. Methods: From January to December 2003, 879 S. pneumonia isolates from the respiratory tractcollected in eight microbiology laboratories in Slovenia were studied fortheir susceptibility to several antimicrobials and for the phenotype of resistance to macrolides. Results: All the isolates tested were susceptible tovancomycin, levofloxacin and moxifloxacin; 16.6% of strains were intermediately resistant and 0.5% were resistant to penicillin. Intermediate resistance to cefotaxim was established in 0.2% of strains, and no resistance in 0%. The rate of resistance to trimethoprim-sulfamethoxazole was 27%, to tetracycline 12.2%, to erythromycin 12.3% and to clindamycin 9.8%. Considerable differences in the rate of resistance to some antibiotics were found between the regions studied. Conclusions: The established rates of resistance to the antimicrobials tested provide the basis for appropriate choice of antibiotic therapy. There were no significant differences in resistance rates between the year 2003 and the previous two years.
Keywords: antibiotic; antibiotiki; bacteria; bakterije; microbiology; mikrobiologija; odpornost; Streptococcus pneumoniae